Transformation of Gender Equality Values in the Household from an Islamic Family Law Perspective - Akmal, Muhammad; Sudirman, Sudirman; Agus Muchsin,; Rusdaya Basri,; Zaenal Said, (MIZAN: JOURNAL OF ISLAMIC LAW, 2026)
This study explores the transformation of gender equality values in Muslim households in Soppeng Riaja Subdistrict, Barru Regency, South Sulawesi, Indonesia, a rural area showing relatively advanced gender equality practices in public sectors such as governance, education, and health, while maintaining traditional role divisions in primary sectors. Employing a qualitative approach with a normative-sociological perspective, the research combines in-depth interviews with six purposively selected married women who balance domestic responsibilities and public work, non-participant observation, and documentation over six months. Findings reveal that gender equality is implemented through three key dimensions: justice (evident in deliberative decision-making and equal educational access), togetherness (reflected in flexible domestic task-sharing based on situational needs), and responsibility (demonstrated by women’s active economic participation and financial management). The community adapts to these changes through gradual strategies, including shifting mindsets toward mutual understanding, reinterpreting religious and cultural beliefs to emphasize Islamic principles of justice and partnership, and altering daily behaviors to foster cooperation. Despite progress, challenges persist, including patriarchal cultural remnants, women’s double burden, and limited understanding of gender equality concepts. The study concludes that gender equality in this context emerges adaptively by harmoniously integrating Islamic teachings, Bugis-Makassar customs, and modern demands, offering a contextual model for Muslim communities in Indonesia without rejecting traditional or religious values. Keywords: gender equality; household transformation; Islamic family law; Maqashid al-Syariah; rural Muslim community.